Β-Carbonyl Substitution on Dimethylaminophenalenones, Halogen-Free Enhancement of Singlet Oxygen Generation in Protic Media - Silva-Molina, C; Silva-Molina, C; Sandoval-Altamirano, C (Elsevier Ltd, 2025)
The incorporation of a β-carbonyl substituent into the push-pull fluorophore donor has been reported as a successful strategy to enhance fluorescence in polar protic media, due to the blockade of non-radiative decay pathways. Nevertheless, to our knowledge, there are no reports of the use of this strategy to improve intersystem crossing (ISC) process. The approach would be particularly useful for photosensitizers whose ability to generate singlet oxygen is impaired in polar protic solvents. We have previously reported dimethylamino-substituted phenalenones that exhibit values of ΦΔ close to unity in non-polar solvents (like hexane), but this value is reduced, tending to be negligible, when moving to polar protic solvents such as methanol and water. Here we present β-carbonyl derivatives of these phenalenones, one of which presented a 20-fold increase in fluorescence and 10-fold increase in singlet oxygen generation in polar protic media when compared to the parent dimethylamino derivative. Thus, we demonstrate that incorporation of a β-carbonyl substituent directly attached to the donor amino group is a suitable strategy that blocks the non-radiative decay pathways of the singlet excited state, promoting fluorescence and also enhancing singlet oxygen generation, ultimately providing enhanced halogen-free photosensitization. © 2024 Elsevier Ltd